The Influence of Problem Based Learning (PBL) Model Collaborative and Learning Motivation Based on Students’ Critical Thinking Ability Science Subjects in Class V State Elementary School 105390 Island Image - Siti Khairani; Retno Dwi Suyanti; Daulat Saragi (BIRCU, 2020)
The study aims to determine the influence of the Problem Based Learnimg (PBL) learning model and the motivation to students critical thinking skills, as well as the interaction between learning models and the motivation to learn from students critical thinking skills. This study was conducted at SD Negeri 105390 in the even semester of the 2019/2020 school year. The population in this study is a class V student of elementary school 105390 Island pictures numbering at 55 people. Sampling is carried out in total, i.e. V-A and V-B classes. The V-B class as an experimental class taught with a collaborative problem-based learning (PBL) model with the number of students 28 people. As for the control class is taught by a direct instruction model elected class V-A with the number of students as many as 27 people. This type of research includes research quasi experiments with 2x2 factorial design with analytical techniques variance (ANAVA) 2 lines. Based on the results of the analysis and research findings from the field obtained several conclusions that are answers to questions on the problem formulation, among them the critical thinking ability of students taught with a collaborative Problem-based learning model better than students taught with a direct learning model (sig. = 0.000 < 0.05), a student's critical thinking ability of high motivation is better than a low-motivation student (sig. = 0.01 < 0.05), and there is interaction between the two learning models with a level of motivation in influencing students ' critical thinking ability (sig. = 0.02 < 0.05).